Observasi Klinik Penggunaan Obat Sariawan pada Remaja: Clinical Observation on the Use of Oral Thrush Medication for Adolescent - Sitti Mujahida Tahir; Niken Indriyanti; Siti Rouchmana (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Thrush is a disease of the oral mucosa that is often experienced by the public. There are various options in curing thrush such as using synthetic drugs containing antiseptics or analgesics. In healing canker sores itself can also use other alternatives such as the use of natural materials that have a function as analgesics. This study aims to determine the types of canker sore treatments used by adolescents today and the effectiveness of these treatments. The method of this study is observational with the number of respondents to date is 70 respondents selected based on inclusion criteria. The results showed that there were 22 respondents who used drugs containing vitamin c. In addition there were also Triamsinolon acetonide 1 mg, Povidone Iodine, phenol crystal 14%, Policrusulen, Borax Glycerine gom 10%, Nystatin, Dequalinium chloride, with alternative treatments such as, drugs containing Glycyrrhizae Glabra Radix and Sophorae Tonkinesis Radix, Betel Black, Salt, Honey, Tomatoes, Aloe Vera Extract, Tamarind. The effectiveness of treatment is seen from the duration of treatment where the average duration of the entire treatment is 6-7 days. It was concluded that the most common treatment used by respondents was treatment containing vitamin c either in the form of drinks or in the form of chips, while the most effective treatment in terms of the duration of canker sores was the alter treatment. Keywords: Medicine, Thrush, Recurrent Aphthous Stomatitis, Effectiveness Abstrak Sariawan merupakan penyakit pada mukosa mulut yang sering dialami oleh masyarakat. Terdapat berbagai pilihan dalam menyembuhkan sariawan seperti menggunakan obat sintetik yang mengandung antiseptik ataupun analgesik. Pada penyembuhan sariawan ini sendiri dapat juga menggunakan alternatif lain seperti penggunaan bahan alam yang memiliki fungsi sebagai analgesik. Penelitian ini bertujuan untuk mengetahui macam-macam pengobatan sariawan yang digunakan remaja saat ini serta efektivitas dari pengobatan tersebut. Metode dari penelitian ini adalah observasional dengan jumlah responden hingga saat ini adalah 70 responden yang dipilih berdasarkan kriteria inklusi. Hasil penelitian menunjukkan terdapat 22 responden yang menggunankan obat yang mengandung vitamin c. Selain itu terdapat juga Triamsinolon acetonide 1 mg, Povidone Iodine, phenol crystal 14%, Policrusulen, Borax Glycerine gom 10%, Nystatin, Dequalinium chloride, dengan pengobatan alternatif seperti, obat yang mengandung Glycyrrhizae Glabra Radix dan Sophorae Tonkinesis Radix, Sirih Hitam, Garam, Madu, Tomat, Ekstrak lidah buaya, Asam Jawa. Efektivitas pengobatan dilihat dari durasi pengobatan dimana durasi rata-rata dari keseluruhan pengobatan adalah 6-7 hari. Maka didapatkan kesimpulan bahwa pengobatan terbanyak yang digunakan oleh responden adalah pengobatan yang mengandung vitamin c baik berupa minuman maupun dalam bentuk keping, sedangkan efektivitas pengobatan memiliki rata-rata durasi pengobatan 6-7 hari. Kata Kunci: Obat, Sariawan, Stomatitis Aftosa Rekuren, Efektivitas